The effects of focus of attention and task objective consistency on learning a balancing task - Jackson, B. H.; Holmes, A. M. (Research Quarterly for Exercise and Sport, 2011)
The purpose of the current study was to examin the effects of consistency belween focus of attention and task objective on the performance of a balancing task. Specifically, we hoped to further explore thc benefits of an external focus of attention proposed by Wulf and colloagues (1998) by determining whether those benefits are due to the focus-of-attention direction itself, or the relative consistency vvith the task objective. It is hypothesized that participants who are given an extemal focus of attention will outperform those with an internal focus when a typical external task objective is provided, echoing results of previous research. However, it is also hvpothesized that those who are given an internal focus of attention will outperform those given an external focus when the task objective is also internal. It is therefore predicted that having a consistent focus of attention and task objective direction will result in superior performance compared to when those factors are inconsistent.